Towards health for all: Some suggestions to policy makers - Tandon, B.B.; Mehra, Rajneesh (2011)
Providing health care for all by 2000 A.D has been a commitment made by the member countries of WHO in the 1978 Alma Ata Declaration of Health for All. India has fallen short of this target. The model for health care delivery followed so far has been largely responsible for this shortfall. The need for a persistent focus on health cannot be over-emphasised as it is an economic good as well as one of he human capital parameters. Further, the increased focus on making the economy grow in double digits makes it imperative for health of the entire population to be taken care of to ensure the achievement of such high rates of growth. This article critically examines various models of public health care in different countries. In addition it examines efforts of making not only curative health care but also preventive care, as practiced in India. Based on the above, a new policy framework has been suggested covering four areas - (a) participation of beneficiaries in the production and consumption of health care in various forms based on ability to pay for the same; (b) increase the ratio of availability of pre-requisites for health care, both curative and preventive by increasing supply of qualified and trained medical staff and hospital beds; (c) encourage public-private partnership to achieve the provisioning of pre-requisites of health care; and, (d) changing the social fabric where insistence on private practice of the doctors is dissuaded and institutional practice is persuaded. - Reproduced.
Keywords: Health services